Telaah Hadis Tentang Pendidikan - Nasirudin . (Universitas Alma Ata, 2015)
Abstrack The authenticity of hadis is one very crucial and controversial smell in the study of contemporary traditions. This may be caused by an assumption that the traditions of the Prophet theologically normative not get a warranty of Allah, as described above. In addition, the urgent problem of authenticity is seen as closely related to the theological views of the majority of Muslims who consider hadith the Prophet has a very strategic role in order to revitalize the Islamic law. Critical Studies on Hadis-Hadis Relating to Education Departing from the above explanation, the research on the authenticity of hadith is something significant in Islamic intellectual kahazanah. Keywords: Hadits, Critical Studies